Reactions of Unprotected Carbohydrates at the Anomeric Carbon: Methodologies for Protecting Group-Free Synthesis of Glycosides - Dey, Kalyan; Jayaraman, Narayanaswamy (Synlett, 2025)
A direct functionalization of the anomeric carbon of unprotected, hydroxy group–abundant carbohydrates is desirable, as it circumvents the need to overcome protecting group interventions and enables the formation of glycosides in a step- and atom-economical manner. The primary, secondary hydroxy, and hemiacetal functionalities encounter reaction selectivities to permit the formation of glycosides selectively, without affecting the remaining sites. The advantage lies in the reactivity differences that provide a manner by which to achieve the desired selective functionalization, namely, that of the hemiacetal in the present context. This article provides a comprehensive overview of recent advancements in the protecting group-free synthesis of glycosides from the unprotected, hydroxy functionality–rich carbohydrates, primarily, mono- and disaccharides. The discussion highlights topical advancements made with particular emphasis on the concept and the mechanistic rationale. The article is organized with a brief introduction; discussions on the (i) direct synthesis of O-glycosides; (ii) base-mediated-; and (iii) direct anomeric functionalization of unprotected carbohydrates; (iv) formation of glycosyl esters; (v) glycosyl phosphates; (vi) N-glycosyl amides; and (vii) C-glycosides that are formed from protecting groups-free carbohydrates. An outlook of the present status of developments is given in the conclusion.
Keywords: Carbohydrates; Hemiacetal; Glycosylation; Glycoside; Protecting group